Math for kids : fun math games and activities inspired by awesome mathematicians, past and present! with 20+ illustrated biographies of amazing mathematicians from around the world - Rapoport, Rebecca; Chung, Allanna (Kitchen pantry scientist., 2022)
"The Kitchen Pantry Scientist: Math for Kids features biographies of 20+ leading mathematicians, past and present, accompanied by accessible and engaging games and activities to bring the history and principles of math alive"--